Performance of lambs under four levels of dietary supplementation and artificially mix-infected with haemonchus contortus and trichostrongylus colubriformis - Carvalho, Nadino (2021)
The effect of four diets on the performance of Dorper lambs that were artificially mix-infected with 1000 infective larvae (L3) of Haemonchus contortus and 1000 L3 of Trichostrongylus colubriformis every three days for 12 weeks was evaluated. For each diet, one infected group (n = 7) and one control group (n = 4) were set up. The four diets contained the following proportions of hay (H) and concentrate (C): Diet 1-100%H; Diet 2-75%H:25%C; Diet 3-50%H:50%C; Diet 4-25%H:75. All the infected groups showed decreases in mean packed cell volume (PCV) and total plasma protein, especially the Diet 1-infected, which was also the group with the highest fecal egg count. The diets and infection had significant effects (P < 0.05) on daily body weight gain (DBWG), cold carcass weight and daily food consumption. The control and infected groups had mean DBWG (in kg), respectively, of 0.048 and 0.025 with Diet 1; 0.082 and 0.067 with Diet 2; 0.188 and 0.189 with Diet 3; and 0.303 and 0.221 with Diet 4. In conclusion, the infection affected the productive performance regardless of the diet; however, with increased metabolizable protein and energy, the risk of occurrence of anemia and hypoproteinemia diminished.